The New Testament - Drury, John (Knopf, Random House, 1998)
The single most important book in all Christian literature is presented here in the glorious King James Version -- one of the richest sources of English poetry through nearly four centuries. The King James Bible, originally issued in the early 1600s, iscontemporary with Shakespeare's last plays; with the beauty of its language and its rhetorical power, it continues to eclipse any other translation
Keywords: Literature